Textualism and the Future of the Chevron Doctrine - Thomas W. Merrill (Washington University Law Quarterly, 1994)
This Essay offers a preliminary assessment of how textualism and the Chevron doctrine are faring together in the Supreme Court. Part II tracks the progress of these two tenets in recent terms of the Supreme Court. In Part III, I consider some possible explanations for these trends.
Keywords: Chevron U.S.A.; Inc. v. Natural Resources Defense Council 467 U.S. 837 (1984); Judicial review of administrative acts; Law; Textual criticism; United States; Antonin Scalia; Law – Interpretation & amp; construction; Textualism (Legal interpretation)